Penerapan Akupresur dalam Menurunkan Tekanan Darah pada Pasien Hipertensi - Theresia Rima Libertyani; Bangun Dwi Hardika; Lilik Pranata (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Hypertension is a chronic disease with a high prevalence worldwide and is a major risk factor for cardiovascular diseases. The management of hypertension not only relies on pharmacological therapy but also requires non-pharmacological interventions as effective complementary therapy. This study aims to analyze the implementation of health education and acupressure therapy in lowering blood pressure in hypertensive patients. This descriptive study involved three hypertensive patients from RT 35 Lebung Jaya, Talang Betutu Village, Palembang. The intervention included structured health education and acupressure therapy given over three consecutive days, with a duration of 15-20 minutes per session. The results of this study showed a reduction in systolic blood pressure between 10-20 mmHg and diastolic blood pressure between 2-7 mmHg. Additionally, there was an increase in knowledge and medication adherence among the patients. From these results, it can be concluded that the integration of health education and acupressure therapy can be an effective nursing intervention for hypertension management, particularly in a community setting. The implementation of this method is expected to become an alternative approach in managing hypertension within the community with a more holistic approach.